EFISIENSI TEKNIS DAN PERILAKU RISIKO PETANI PADI BERDASARKAN PENGGUNAAN INPUT (STUDI KASUS DI DESA LANGKAP KECAMATAN BURNEH) - Dewi Nafisah; Elys Fauziyah (Universitas Sebelas Maret, 2020)
The need for rice is increasing along with the increasing of Indonesian population growth per year. Burneh sub-district has the largest area in Bangkalan district. One of the main rice producer in Burneh sub-district is Langkap village. The study was conducted on December 2019 with the purpose of analyze the level of technical efficiency and risk behavior based on the inputs allocation used. This study applied double logarithmic risk analysis. The results showed that the production of rice in Langkap village achieved average technical efficiency of 70%. This shows that farmers in Langkap village are not technically efficient. Farmers 'risk behavior in using urea fertilizer and labor inputs are categorized as risk averse (risk aversion), while in application of seed and phonska fertilizers are classified as risk takers.